Augmenting the quality of Acehnese knowledge-based EFL material through a 4D model - Usman, Jarjani; Ibrahim, Lukman (Studies in English Language and Education, 2023)
Integrating local knowledge into English learning material is crucial in this globalized era as it has multiple functions, such as building students identity, motivating them to learn, making them attached to their culture, and preserving their local knowledge. Anchored by the curriculum theory, this study systemically developed an Acehnese Islamic cultural knowledge-based lesson material for learning English by students at senior high school and analyzed its quality based on the curriculum perspective. In doing so, this study involved EFL teachers using Tiagarajans 4D (Define-Design-Develop-Disseminate) model for developing the English learning material as a supplementary material for senior high schools. Local knowledge, such as Molod Nabi, Meuleumak, and Toroyong, was selected to be its content. Its quality was then assessed based on the quality criteria of a curriculum product, such as validity and practicality. The results revealed that the Acehnese local culture knowledge-based EFL lesson material for senior high schools is valid based on the teachers perceptions. It contains state-of-the-art knowledge and is practical for teaching English to foster the deradical characters of senior high school students. In conclusion, using the 4D model in collaboratively developing the local knowledge-based EFL English lesson material is beneficial for producing high-quality curriculum products.